Transcriptional Regulation of the Daptomycin Gene Cluster in Streptomyces roseosporus by an Autoregulator, AtrA (J Biol Chem, 2015)
Daptomycin is a cyclic lipopeptide antibiotic produced by Streptomyces roseosporus. To reveal the transcriptional regulatory mechanism of daptomycin biosynthesis, we used the biotinylated dptE promoter (dptEp) as a probe to affinity isolate the dptEp-interactive protein AtrA, a TetR family transcriptional regulator, from the proteome of mycelia. AtrA bound directly to dptEp to positively regulate gene cluster expression and daptomycin production. Meanwhile, both ΔatrA and ΔadpA mutants showed bald phenotype and null production of daptomycin. AdpA positively regulated atrA expression by direct interaction with atrA promoter (atrAp), and removal of ArpA in S. roseosporus, a homolog of the A-factor receptor, resulted in accelerated morphological development and increased daptomycin production, suggesting that atrA was the target of AdpA to mediate the A-factor signaling pathway. Furthermore, AtrA was positively autoregulated by binding to its own promoter atrAp. Thus, for the first time at the transcriptional level, we have identified an autoregulator, AtrA, that directly mediates the A-factor signaling pathway to regulate the proper production of daptomycin.